Rotavirus-associated acute diarrhea outbreak in West Shewa Zone of Oromia Regional State, Ethiopia, 2017 - Abyot Bekele Woyessa; Almaz Abebe; Berhane Beyene; Mesfin Tefera; Esete Assefa; Hiwot Ketema; Birke Teshome; Ayenachew Bekele; Yohanis Dugasa; Shambel Habebe; Zewdu Assefa; Diriba Sufa; et al. (The Pan African Medical Journal, 2019)

(untitled)
INTRODUCTION: Rotavirus causes severe-diarrheal diseases in infants. An estimation of 138 million rotavirus-associated diarrheal cases and 215,000 deaths occur every year globally. In December 2016, West-Shewa zone in Ethiopia reported unidentified gastrointestinal diarrhea outbreak. We investigated to identify the causative agent of the outbreak to support response operations. METHODS: Medical records were reviewed, and the daily line list was collected from health facilities. Descriptive data analysis was done by time, person and place. Stool specimens were first tested by antigen capture enzyme immunoassay (EIA) technique and further confirmed by reverse-transcription polymerase chain reaction (RT-PCR) as a gold standard. The product of RT-PCR was genotyped for each gene using G1-G4, G8-G9 and G12 primers for VP7 gene and P(4), P(6), P(8) and P(14) primers for VP4 gene. RESULTS: A total of 1,987 diarrheal cases (5.7 per 1000) and five deaths (case-fatality rate 0.25%) were identified and epidemiologically-linked to confirmed rotavirus from December 2016 to February 2017. Among the cases, 1,946 (98%) were 5 children. Fourteen (74%) of the 19 tested stool specimens were positive for rotavirus by EIA and RT-PCR. Majority of strains detected were G12P(6) (25%) and G-negative P(8) (25%) followed by G9P(8) (19%), G1P(8) (13%) and G3/G2 P(8), G12P(8), and G-negative P(6) (6% each). CONCLUSIONS: Diarrheal outbreak which occurred in West-Shewa zone of Ethiopia was associated with rotavirus and relatively more affected districts with low vaccination coverage. Routine rotavirus vaccination quality and coverage should be evaluated and the surveillance system needs to be strengthened to detect, prevent and control a similar outbreak.